Measurement and identification of areas susceptible to flood spreading from the viewpoint of geological formations in Birjand watershed using RS / GIS - Parviz Ziaiian Firouz Abadi; Ayoub Badragh Nejad; Reza Sarli; Mahboub Babaie (تحقیقات کاربردی علوم جغرافیایی)
Rivers are the natural flow of surface waters that flow in a certain bed seasonal or permanently. Rivers include a vast range of narrow waterways and with mountainous high steep to low steep and wide beds flowing in plains. However, rivers have had an effective role in urban development and human civilization, therefore, identification of flood prone areas and flood part in the potent lower fields of Birjand watershed would lead to aid feeding the artificial environment of the water shed and would also lead to increase of quality in the environment fields. The purpose of this study is to identify the environment about the river and evaluating the danger in case of occurrence of flood crisis. All of the processes and analyses of data were performed in the GIS atmosphere utilizing the three methods of saw Fuzzy, AHP and Boleyn logic for weighting data such as (gradient, erosion, land application, watershed system, soil, geological fault distribution, quaternary unit, level of underground waters, and satellite imagery) and the potent areas in terms of confronting danger were located. The results of the study showed that the areas that the effort for exploiting floods was made have characteristics such as (existence of alluvium and colluvium sediments in the high steep feet of the slopes and watersheds with major stone occurrences, existence of fan-shaped sediments and alluvial fan in the external aperture of dry rivers and water ways with mountainous watersheds and hills leading to low steep fields, existence of low fields from the manner of altitude in proportionate to fields near). Finally, the best model that could present a better evaluation and conclusion about this matter was the Boleyn logic model in locating the flood part.